2017
DOI: 10.1136/ejhpharm-2016-001192
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient satisfaction in an outpatient hospital pharmacy

Abstract: ObjectiveTo analyse the factors leading to greater satisfaction among patients attending the outpatient hospital pharmacy (OPh).MethodsA cross-sectional study was conducted of patients attending the OPh of a 1250-bed university hospital. A self-administered questionnaire for measuring outpatients' satisfaction was developed. Global satisfaction was measured on a scale of 1 to 10. Indices of perceived quality for accessibility, interpersonal professional–patient relationship and the convenience of the process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
5
20
1
1
Order By: Relevance
“…Moreover, various other studies conducted in KSA where study population majorly comprised of young patients showed no relationship of patients`satisfaction with age [ 10 , 12 ]. In another study conducted in Spain, age was not significantly associated with satisfaction [ 4 ]. Recently, Aziz et al (2018) found higher satisfaction score among patients with age ranging from 26 to 30 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, various other studies conducted in KSA where study population majorly comprised of young patients showed no relationship of patients`satisfaction with age [ 10 , 12 ]. In another study conducted in Spain, age was not significantly associated with satisfaction [ 4 ]. Recently, Aziz et al (2018) found higher satisfaction score among patients with age ranging from 26 to 30 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists, in collaboration with other health professionals, have a responsibility to improve the quality of care among patients [ 4 , 5 ]. Since the healthcare system has shifted from episodic care to population health management and from volume to value-based care, the role of pharmacists and their contribution has been emphasized in treatment and prevention of chronic diseases and their related complications [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Consequently, Administrations that offers more high-class pharmaceutical health care to their patients do establish prominent levels of satisfaction. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…The quality of services provided by the pharmacist, including the information given to patients, his/her attempts to resolve patients' doubts, his/her care for patients, and the amount of time devoted to patients' personal attention and time devoted to patients, was the most important factor predicting patient satisfaction. [ 16 ] In another study, patients' satisfaction regarding pharmacy services in the medication therapy management clinic was assessed. The results showed that the overall satisfaction did not significantly correlate with age, gender, ethnicity, and number of comorbidities.…”
Section: Discussionmentioning
confidence: 99%